Disentangling the Nexus of Leadership Styles, Job Satisfaction, and Organizational Commitment: A Study on the Public Hospitals of Tigray, Ethiopia - Mebrahtu Woldu; P. C. K. Rao (Revista Electronica de Veterinaria, 2024)
This study delves into the complex dynamics between leadership styles and organizational commitment, emphasizing the mediating influence of job satisfaction among nursing professionals in public hospitals across the Tigray region of Ethiopia. Utilizing a robust cross-sectional research design, data was collected from 568 head and staff nurses through a structured survey instrument. The analytical approach involved a comprehensive application of both SPSS 20 for regression analysis and AMOS for structural equation modeling (SEM), offering a nuanced understanding of both direct and indirect relationships between leadership behaviors and organizational outcomes. Results indicate that transformational leadership exerts a profound positive influence on both job satisfaction and organizational commitment, while transactional leadership, although beneficial, demonstrates a comparatively scrawnier impact. The pivotal role of job satisfaction as a mediator underscores the necessity for healthcare institutions to cultivate an environment conducive to the professional and emotional well-being of their nursing staff, which in turn fortifies their commitment to organizational goals and improves patient care outcomes. The study’s findings suggest the urgent need for targeted leadership development initiatives, particularly those aimed at enhancing transformational leadership competencies and empowering women leaders within the healthcare system. Additionally, ongoing leadership training is recommended to equip nursing supervisors with the skills necessary to foster job satisfaction and, consequently, elevate organizational commitment.